1995
DOI: 10.1016/s1078-5884(05)80110-8
|View full text |Cite
|
Sign up to set email alerts
|

The “ad hoc” estimation of outflow does not predict patency of infrainguinal reconstructions

Abstract: The estimation of outflow from angiography seems to be of no value in predicting graft patency in infrainguinal grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…3 Another study failed to find a definite correlation between autogenous graft patency and the quality of distal runoff. 24 A number of authors studying infrainguinal angioplasty alone have found that runoff status significantly affects the success of these endovascular interventions. 14,25 The effect of runoff on stented femoral and popliteal vessels is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…3 Another study failed to find a definite correlation between autogenous graft patency and the quality of distal runoff. 24 A number of authors studying infrainguinal angioplasty alone have found that runoff status significantly affects the success of these endovascular interventions. 14,25 The effect of runoff on stented femoral and popliteal vessels is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Some predictions on bypass patency can be made using the Society for Vascular Surgery/International Society for Cardiovascular Surgery system, although contradicting results on the reliability of this tool have been reported. [11][12][13][14][15][16][17] Various methods of intraoperative bypass quality assessment are at the surgeon's disposal, of which angiography is the reference standard. Angiography, however, is relatively timeconsuming.…”
mentioning
confidence: 99%
“…A arteriografia pré-operatória, apesar de ser o méto-do mais utilizado e considerado padrão-ouro, pode falhar na definição do prognóstico da revascularização 27 . A Sociedade Norte-Americana de Cirurgia Vascular procurou em duas ocasiões elaborar um sistema de classificação que pudesse melhorar a capacidade da arteriografia no estabelecimento deste prognóstico 28,29 .…”
unclassified
“…A Sociedade Norte-Americana de Cirurgia Vascular procurou em duas ocasiões elaborar um sistema de classificação que pudesse melhorar a capacidade da arteriografia no estabelecimento deste prognóstico 28,29 . Apesar disso e da complexidade dos sistemas de classificação arteriográfica propostos, estudos que observaram a sua aplicação clínica demonstraram resultados contraditórios quanto a sua capacidade de estabelecer o prognóstico do enxerto 27,30,31 .…”
unclassified